Permittivity and performance of dielectric pads with sintered ceramic beads in MRI: early experiments and simulations at 3 T. Issue 1 (13th August 2012) - Luo, Wei; Lanagan, Michael T.; Sica, Christopher T.; Ryu, YeunChul; Oh, Sukhoon; Ketterman, Matthew; Yang, Qing X.; Collins, Christopher M.
Abstract Passive dielectric materials have been used to improve aspects of MRI by affecting the distribution of radiofrequency electromagnetic fields. Recently, interest in such materials has increased with the number of high‐field MRI sites. Here, we introduce a new material composed of sintered high‐permittivity ceramic beads in deuterated water. This arrangement maintains the ability to create flexible pads for conforming to individual subjects. The properties of the material are measured and the performance of the material is compared to previously used materials in both simulation and experiment at 3 T. Results show that both permittivity of the beads and effect on signal‐to‐noise ratio and required transmit power in MRI are greater than those of materials consisting of ceramic powder in water. Importantly, use of beads results in both higher permittivity and lower conductivity than use of powder. Magn Reson Med, 2013. © 2012 Wiley Periodicals, Inc.